Natural Hedging of Exchange Rate Risk: The Role of Imported Input Prices - Dario Fauceglia; Anirudh Shingal; Martin Wermelinger (Swiss Journal of Economics and Statistics, 2014)
In this paper, we estimate ERPT into imported input prices and export prices using disaggregated quarterly trade data for Switzerland over 2004–2011. We find evidence for high pass-through rates into imported input prices. This demonstrates the effectiveness of natural hedging. On the export side, ERPT exhibits substantial sectoral heterogeneity and changes in imported input costs are not transmitted to foreign consumers in most cases. This suggests the use of cheaper imported inputs to offset adverse effects of currency appreciation on export profit margins.
Keywords: F31; F41; 330; exchange rates; exchange rate pass-through; international trade; prices